Energy-related decarbonisation measures selection process model in automotive industry - Sami Succar; Damien Evrard; Daniel Brissaud; Damien de la Fontaine (International Journal of Sustainable Engineering)
Manufacturing companies have the obligation to reduce their environmental impact to ensure their future viability and respect the norms imposed by governmental institutions. To comply with this challenging context, they have designed ambitious strategies at the corporate level and have mobilised the necessary resources. Unfortunately, it is noticed that the practice in the different plants does not give the expected results, in terms of speed of selection, study, and implementation. The main objective of this study is to suggest a new way of accelerating manufacturing plants’ decarbonisation process. For this purpose, the paper analyses the practice of a car manufacturing company in order to understand the principles adopted for decarbonisation process as well as the roles and interactions of its actors. It then proposes a strategic process model for implementing decarbonisation measures in multi-site industrial companies and increasing decarbonisation process acceleration using data. The approach is data-based and consists in a 5-step process model to accompany the transfer of decarbonisation measures from a pilot plant to the others. The decarbonisation process model is being implemented in a large automotive company and the first lessons are drawn. The tools to support the methods will be developed later.